Religious affiliation and the intention to choose psychiatry as a specialty among physicians in training from 11 Latin American countries - Calizaya-Gallegos, Carlo (2018)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.